Family Stressors Experienced by Adolescents in Secondary Schools in Nairobi City County - Ndehi, Violet; Ndung'u, Elijah; Nyagah, Virginia (International Journal of Psychology, 2023)
Purpose: The aim of this study was to determine the different sorts of family stressors among adolescents in secondary schools in Nairobi County have observed. Methodology: The study employed a parallel convergent mixed-method design with a target population of 38,641 adolescents in Nairobi County secondary schools. Quantitative Data was collected from 398 adolescents in forms 2 and 3 via simple random sampling. All school categories were represented through cling cluster sampling, while simple random sampling selected respondents within each school. Qualitative data was purposively obtained from 10 students, 10 parents, and 10 teachers. Proven psychometric tools like Assessment of identity Development in Adolescence, Strengths and Difficulties Questionnaire, Children's Perception of Inter-Parental Conflict Scale, and Dhaka Stress Scale-Adolescent collected quantitative data. Pearson coefficient correlations were calculated using Statistical Package for Social Sciences (SPSS version 25) to explore relationships between variables. Findings: The study established the types of family stressors and confined itself to parental conflict and family changes. The findings of the study revealed that a slight majority of secondary students experienced less intense parental conflict. However, the study results also showed slight high rate of separation, followed by extramarital affairs and divorce among the families' stressors. Additionally, the qualitative data analysis showed that parental conflict, separation, and divorce were among the few family stressors unanimously reported by all three respondent groups (parents, teachers and students). Furthermore, both the students and parents reported domestic violence as one of family stressors. Unique Contribution to Theory, Practice and Policy: The study was anchored on Family Systems Theory. The study recommended the involvement of a counsellor, a chaplain and the government. There should also be a wide spread training of parents and the wider community. These interventions should be implemented not only within schools but also within communities. Therefore, parents, teachers, Non-governmental Organizations, churches, the government and stakeholders in psychological counselling must collaborate and implement interventions. This can create a more robust and holistic support system by adopting a comprehensive approach encompassing educational institutions and community settings.